Analisis keterampilan pemecahan masalah materi operasi hitung pembagian pada peserta didik sekolah dasar - Aisyah Al Rohmah; Siti Kamsiyati; Sukarno Sukarno; Tri Suprapti (Universitas Sebelas Maret, 2019)
Abstract. This research is implemented as a recommendation for the other research about problem-solving skills in the division material for grade 2 elementary school students. Division counting operation is basically in a calculation. Actually, counting in operation is often implemented for solving problems. The technique of taking research subjects using purposive sampling technique. The data in this research is collected by some technique such as interview and observation as main techniques, then documentation and test as supporting techniques. The validity of the data used in this study is triangulation by testing the validity of credibility, transferability, dependability, and confirmation. The analysis of the data used is component analysis. The result of the analysis shows that students in grade 2 have enough skills, this result measured by scoring guidelines that have been consulted by expert lecturers by calculating descriptors that appear on each indicator, this is evident from the emergence of 2 indicators of the total 4 indicators. This is evidenced by two indicators from four indicators used in this research. The two indicators, there are understanding the problem and implementing a plan. While two other there is crosscheck the result and problem-solving process are not yet appeared. It can be concluded that grade 2 students in SDN Tunggulsari 1 No. 72 of the academic year 2018/ 2019 have sufficient problem-solving skills in the division material. Keywords: analyze, problem solving skills, elementary school, and indicators